(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This article discusses environmental problems that are currently considered urgent on both global and regional scales, their causes, and measures for their prevention. The impact of such environmental issues as air pollution, depletion of water resources, soil degradation, waste problems, and reduction of biodiversity on human health and the economy is analyzed. In addition, the practical significance of modern methods for solving environmental problems, resource-saving technologies, renewable energy sources, and environmental monitoring systems is described.